Effects of Naphthalene on the Performance of Ni/YSZ Anode-Supported SOFCs. (10th July 2019) - Hauser, Michael; Herrmann, Stephan; Hauck, Maximilian; Fendt, Sebastian; Jeong, Hyeondeok; Lenser, Christian; Menzler, Norbert H.; Spliethoff, Hartmut
Abstract : The operation of SOFCs on biomass-derived fuels demands an intrinsic tolerance of the cells towards biogenic contaminants like tars. In order to develop more robust cells, the behaviour of state-of-the-art Ni/YSZ anode supported cells at 700 °C in presence of naphthalene as model tar was extensively studied. As reported in literature naphthalene blocks the active sites of nickel catalysts and therefore hinders the utilisation of methane and carbon monoxide in the fuel gas. This study shows that the loss in performance is greater than only the contribution of this inertisation of CH4 and CO and that the behaviour of the cell voltage is similar to the poisoning with H2 S. We also found that the operation temperature is a major parameter when tolerance limits for naphthalene have to be defined. The analysis of electrical impedance data helped to understand the underlying poisoning processes.